A phase I/II escalation trial design T-RAD: Treatment of metastatic lung cancer with mRNA-engineered T cells expressing a T cell receptor targeting human telomerase reverse transcriptase (hTERT) - Maggadóttir, Sólrún Melkorka; Kvalheim, Gunnar; Wernhoff, Patrik; Sæbøe-Larssen, Stein; Revheim, Mona-Elisabeth; Josefsen, Dag; Wälchli, Sébastien; Helland, Åslaug; Inderberg, Else Marit (Frontiers in Oncology, 2022)
Background: Adoptive cellular therapy (ACT) with genetically modified T cells aims to redirect T cells against resistant cancers through introduction of a T cell receptor (TCR). The Radium-4 TCR was isolated from a responding patient in a cancer vaccination study and recognizes the enzymatic component of Human Telomerase Reverse Transcriptase (hTERT) presented on MHC class II (HLA-DP04). hTERT is a constitutively overexpressed tumor-associated antigen present in most human cancers, including non-small-cell lung cancer (NSCLC), which is the second most common type of cancer worldwide. Treatment alternatives for relapsing NSCLC are limited and survival is poor. To improve patient outcome we designed a TCR-based ACT study tageting hTERT. Methods: T-RAD is a phase I/II study to evaluate the safety and efficacy of Radium-4 mRNA electroporated autologous T cells in the treatment of metastatic NSCLC with no other treatment option. Transient TCR expression is applied for safety considerations. Participants receive two intravenous injections with escalating doses of redirected T cells weekly for 6 consecutive weeks. Primary objectives are safety and tolerability. Secondary objectives include progression-free survival, time to progression, overall survival, patient reported outcomes and overall radiological response. Discussion: Treatment for metastatic NSCLC is scarce and new personalized treatment options are in high demand. hTERT is a tumor target applicable to numerous cancer types. This proof-of-concept study will explore for the first time the safety and efficacy of TCR mRNA electroporated autologous T cells targeting hTERT. The T-RAD study will thus evaluate an attractive candidate for future immunotherapy of solid tumors.